(untitled) (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Preoperative fasting is a major concern to protect the gastric aspiration which is very dangerous. However overnight fasting is uncomfortable and has many deleterious effects on the human body. In many countries fasting until 2 to 3 hours before surgery has been practiced but in Bangladesh, overnight fasting is still being practiced in routine cases. Objectives: The objective of this study was to compare the effectiveness between preoperative overnight fasting and oral rehydration solution administration until two hours before abdominal surgery under general anaesthesia. Methods: A total of 100 patients of ASA (American Society of Anesthesiologist) class I and II, age above 18 years, and BMI < 30 kg/m2 were scheduled for abdominal surgery under GA (General Anaesthesia) were included in this study. Then all patients were randomized into two groups as patients who were on overnight fasting for 10 hours (Group A-Controlled, n=50), and patients who were on ORS until 2 hours before abdominal surgery (Group B-ORS, n=50). All patients had their last meal at 11 AM before the day of surgery. Patients in group A will not take anything orally or via any route, except their ongoing vital medications if present. Patients in group B received 500 ml of standard ORS in the early morning on the day of surgery after waking up from bed (from 05 AM to 06 AM) and another 500 ml until 2 hours before the surgery (06 AM to 07 AM). As the primary outcome gastric residual volume and gastric fluid pH in both group was measured immediately after anaesthesia induction. Several physiological measures (thirst and hunger, nausea/vomiting, cognitive function) were measured with the help of a preformed questionnaire. Results: Mean gastric residual volume immediately after induction was statistically significant (p<0.05) between the two groups. However, the mean gastric fluid pH was statistically insignificant (p>0.05). The ORS group (Group B) became less thirsty before surgery (P=0.001). Postoperative nausea/vomiting (PONV) was less in group B (P=0.029) than in group A. The patient’s recovery time was significantly less in ORS group (P=0.003). Postoperative cognitive performance was better in group B (P=0.001). Conclusions: Oral rehydration solution administration until two hours before surgery is effective and can be considered routinely before abdominal surgery conducted under general anaesthesia except for delayed gastric emptying. J Shaheed Suhrawardy Med Coll 2022; 14(1): 20-27